NEURO-BEHAVIORAL RESPONSES TO FINANCIAL RESTATEMENT DISCLOSURES: AN FNIRS EXPERIMENTAL STUDY - Yuyun Yuniarti Layn; Arifuddin Arifuddin; Mediaty Mediaty (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study aims to comprehensively examine individuals' neurobehavioral responses to financial restatement disclosures through a literature review approach, focusing on the use of functional Near-Infrared Spectroscopy (fNIRS) technology in accounting and behavioral finance research. Financial restatements are often perceived as negative signals that can influence investors' risk assessments, trust, and economic decisions. Through a search and analysis of relevant international academic literature, this study synthesizes empirical findings linking cognitive and emotional processes with brain activity, particularly in the prefrontal cortex, which plays a role in decision-making and financial information processing. This study also examines how an fNIRS-based experimental design is used to capture the dynamics of neurophysiological responses when individuals are exposed to financial restatement information. The results of the literature review indicate that financial restatement disclosures trigger complex neurobehavioral responses, reflecting increased cognitive load, sensitivity to risk, and changes in attitudes and decision-making behavior. Furthermore, the existing literature indicates that non-invasive neuroimaging approaches such as fNIRS have great potential to enrich our understanding of the internal mechanisms underlying market reactions to accounting information. This research provides theoretical contributions by formulating an integrative conceptual framework between accounting, behavioral finance, and neuroscience, and methodological contributions by highlighting the opportunities and challenges of using fNIRS in experimental studies in financial reporting.